Body dysmorphic disorder: a treatment synthesis and consensus on behalf of the International College of Obsessive-Compulsive Spectrum Disorders and the Obsessive Compulsive and Related Disorders Network of the European College of Neuropsychopharmacology. (20th November 2020) - Castle, David; Beilharz, Francesca; Phillips, Katharine A.; Brakoulias, Vlasios; Drummond, Lynne M.; Hollander, Eric; Ioannidis, Konstantinos; Pallanti, Stefano; Chamberlain, Samuel R.; Rossell, Susan L.; Veale, David; Wilhelm, Sabine; et al.
Abstract : Body dysmorphic disorder (BDD) is characterized by a preoccupation with a perceived appearance flaw or flaws that are not observable to others. BDD is associated with distress and impairment of functioning. Psychiatric comorbidities, including depression, social anxiety, and obsessive-compulsive disorder are common and impact treatment. Treatment should encompass psychoeducation, particularly addressing the dangers associated with cosmetic procedures, and may require high doses of selective serotonin reuptake inhibitors* (SSRI*) and protracted periods to establish full benefit. If there is an inadequate response to SSRIs, various adjunctive medications can be employed including atypical antipsychotics*, anxiolytics*, and the anticonvulsant levetiracetam*. However, large-scale randomized controlled trials are lacking and BDD is not an approved indication for these medications. Oxytocin* may have a potential role in treating BDD, but this requires further exploration. Cognitive-behavioural therapy has good evidence for efficacy for BDD, and on-line and telephone-assisted forms of therapy are showing promise. CBT for BDD should be customized to address such issues as mirror use, perturbations of gaze, and misinterpretation of others' emotions, as well as overvalued ideas about how others view the individual.